Achievement-Based Celebrities As Objects & Instruments Of Consumption - Zarkada, Anna K.; Tzoumaka, Eugenia; Siomkos, George; Panigyrakis, George G. (My University, 2014)
Celebrities dominate the public sphere as protagonists of the media spectacle. This qualitative research project investigates consumer behaviour towards achievement based celebrities using football players as an example. The data presented here are drawn from critical incidents collected through five focus groups with a total of 31 participants in the two major cities of the country. We conceptualize celebrities as instruments and objects of consumption in multiple and diverse ways. The results confirmed earlier empirical studies of isolated consumption modes and added new ones, previously unexplored, consumption patterns thus setting the scene to further elaborate emergent theory. The analysis provides a framework of categorizing the modes of consuming celebrities. It is demonstrated that footballers are commodified primarily as objects and their instrumental role (e.g. as endorsers) is secondary.
Keywords: achievement based celebrity; consumer behaviour; objectified and instrumental consumption